7xxx series aluminum alloy with high softening resistance for nuclear power and preparation method of 7xxx series aluminum alloy
By regulating the five-time symmetric quasi-crystal structure and controlling the nano-strengthening phase size, the problem of weakening the strengthening capacity of 7xxx aluminum alloy at high temperatures is solved, and stable service in the high-temperature environment of nuclear power plants is achieved.
Patent Information
- Application Number
- CN202510877942.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2025-08-15
AI Technical Summary
The existing 7xxx aluminum alloys have rapidly roughened the nanoprecipitation phase in an environment above 120°C, resulting in weakening of strengthening capabilities and making it difficult to serve in the extreme working environment of nuclear power plants.
By regulating the five-time symmetric quasi-crystalline structure, the size growth of the nanostrengthening phase is controlled, and specific alloy compositions and heat treatment processes are adopted, including the combination of alloy elements Zn, Mg, Cu and microalloy elements Sc, Er, Y, Yb, Ag, Ca, Sb, Pb, Bi, Te, combined with smelting, homogenization, rolling, solid solution and aging treatment, a small nanostrengthening phase is formed.
It significantly improves the high-temperature softening ability of 7xxx series aluminum alloy, so that it maintains good strength within the range of 150-250℃, and is suitable for lightweight high-temperature structural materials for nuclear power.
Smart Images

Figure CN120485614A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a 7xxx series aluminum alloy with high strength and softening resistance for nuclear power and a preparation method thereof, and more particularly to a 7xxx series aluminum alloy with overheating resistance and a preparation method thereof, belonging to the field of metal material processing technology. Background Art
[0002] 7xxx series aluminum alloys are the most widely used aluminum alloy series in aerospace applications and are widely used in aircraft components. As heat-strengthened aluminum alloys, the primary strength contribution of 7xxx series aluminum alloys comes from the obstruction of dislocation motion by nano-precipitates generated during the aging process. The size and number density of these nano-precipitates have a significant impact on strengthening. Generally speaking, the smaller the size and the higher the number density of the nano-precipitates, the greater the strengthening ability. The number density of nano-precipitates is generally related to the alloying composition: the higher the alloying composition, the higher the number density of strengthening phases that can precipitate. The size of the nano-precipitates is significantly related to temperature. As the temperature increases, the elements that constitute the nano-precipitates diffuse faster, causing their size to increase significantly. When the temperature exceeds 120°C, the nano-precipitates in 7xxx series aluminum alloys will rapidly coarsen, weakening or even losing their strengthening ability, making it difficult for 7xxx series aluminum alloys to serve in environments above 100°C.
[0003] With the development of my country's nuclear power industry, the extreme operating environments of nuclear power plant reactors have posed challenges to the heat resistance of components. Therefore, improving the heat resistance of 7xxx series aluminum alloys and developing 7xxx series aluminum alloys with resistance to high-temperature softening are imperative. The high strength and softening resistance of aluminum alloys ensure their stability and durability in nuclear power applications, thereby guaranteeing the safe operation of nuclear power plants. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to propose a method for controlling the size growth effect of the nano-reinforced phase of 7xxx series aluminum alloys under high temperature environment by regulating a five-fold symmetric quasicrystal structure, thereby improving the high-temperature softening resistance of 7xxx series aluminum alloys and improving their high-strength and softening-resistant 7xxx series aluminum alloys for nuclear power with a service temperature of 150-250°C.
[0005] At the same time, the present invention provides a method for preparing a 7xxx series aluminum alloy with high strength and softening resistance for nuclear power.
[0006] At the same time, the present invention provides an application of a 7xxx series aluminum alloy with high strength and softening resistance for nuclear power.
[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is: The present invention involves the design of alloy compositions and the coordination of heat treatment processes. The primary alloying elements of the 7xxx series aluminum alloys involved are: Zn 6-12 wt.%, Mg 1.0-6.0 wt.%, and Cu 0-3.0 wt.%. Required microalloying elements include one or two of the following to promote the formation of a quintic-symmetric quasicrystal structure: Sc, Er, Y, Yb, Ag, Ca, Sb, Pb, Bi, and Te, with a microalloying content of 0.2-2.5 wt.%. The balance is Al and unavoidable impurities.
[0008] The preparation method of the 7xxx series aluminum alloy resistant to overheating and softening is as follows: S1. Prepare the materials according to the alloy mass percentage requirements; S2. The prepared metal material is smelted at a high temperature of 700-760°C in a melting furnace, and a certain amount of slag remover is added. The slag remover is a chloride-fluoride composite slag remover, and the addition amount is equivalent to 0.1-0.3wt% of the metal material. The liquid metal is deslagging and argon degassing and refining. Specifically, the slag remover is evenly sprinkled on the surface of the liquid metal and gently stirred. Specifically, a graphite rotor is used for stirring at a speed of 400-600r / min to promote slag-gas separation. After stirring, the slag is allowed to stand for 10-30 minutes to skim off the slag; S3. The liquid metal is then poured into a mold and solidified to form a 7xxx aluminum alloy ingot material; S4. Homogenize the ingot material by holding it at 250-400°C for 5-6 hours, then at 450-470°C for 10-24 hours. Quench it with air cooling at room temperature. S5. Roll the homogenized sample. The process is to heat at 420-450℃ for 1-5 hours, use multiple hot rolling process, with a single pass reduction of 5-10%, and a total hot rolling reduction of 50-80%. Then air cool to room temperature, and then perform multiple cold rolling process at room temperature, with a single pass reduction of 5-10%, and a total cold rolling reduction of 50-80%. S6. The rolled plate is subjected to solution treatment at 250-400°C for 2-3 hours, followed by 475-480°C for 2-5 hours. The quenching process is performed in warm water at 25-80°C. S7. After solution quenching, the material is aged. This aging process can produce a nano-reinforced phase with a quintic-symmetric quasi-crystalline structure in the alloy with the aforementioned composition ratio, thereby controlling the size of the nano-reinforced phase. The specific aging process is as follows: Step 1) Hold the sample at 100-150°C for 1 hour. Step 2) Pre-deform the sample from the previous step by 2-8% tensile strain. Step 3) Hold the sample from the previous step at 120-180°C for 24-100 hours. The sample is placed in the furnace after the furnace temperature reaches the temperature corresponding to Step 3).
[0009] The present invention has the following beneficial effects: The present invention designs a new alloy composition by controlling the contents of the main alloying elements Zn, Mg, and Cu, while simultaneously adding the microalloying elements Sc, Er, Y, Yb, Ag, Ca, Sb, Pb, Bi, and Te. By combining the element ratios with the heat treatment process to control the formation of a quintic-symmetric quasicrystal structure, the size of the nano-reinforcement phase is controlled. 7xxx aluminum alloys with this quintic-symmetric quasicrystal structure exhibit significant resistance to high-temperature softening.
[0010] The present invention relates to a 7xxx series aluminum alloy with overheat resistance and a preparation method thereof. The overheat resistance is regulated by controlling the size of its nano-reinforced phase based on a quintic symmetric quasicrystal structure. The control method relates to the composition design of the alloy material and the coordination of heat treatment, and belongs to the technical field of metal materials. The main components of this series of alloys include the following components by mass percentage: Zn 6-12 wt.%, Mg 1.0-6.0 wt.%, Cu 0-3.0 wt.%. Secondly, any one or more of Sc, Er, Y, Yb, Ag, Ca, Sb, Pb, Bi, and Te need to be added, and the content of each added element is 0.2-2.5 wt.%, and the balance is Al and unavoidable impurities. A method for controlling a quintic-symmetric quasicrystal structure comprises first formulating an alloy material by mass percentage according to the aforementioned composition, producing an ingot through a melt-casting process, homogenizing the ingot, then rolling it, solutionizing the rolled sample, and then subjecting the rolled sample to an aging process. The aging process, combined with the aforementioned composition ratio, generates nano-precipitates containing quintic-symmetric structures, and the size of the nano-precipitates is controlled by the number of quintic-symmetric structures. The 7xxx series prepared by the present invention exhibits excellent performance and resistance to overheat softening, and can be used as lightweight, high-temperature structural materials for nuclear power plants. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 1 is a microstructure diagram of the thermal softening resistant 7xxx aluminum alloy prepared by the present invention, wherein (a) is Example 1, (b) is Example 2, and (c) is Example 3; Figure 2 7xxx aluminum alloys prepared in comparative examples, wherein (a) is comparative example 1 and (b) is comparative example 2; Figure 3 1 is a diagram of the nano-strengthening phase structure of the overheat softening resistant 7xxx aluminum alloy prepared by the present invention, wherein (a) is Example 1, (b) is Example 2, and (c) is Example 3; Figure 4 2 is a nano-strengthening phase structure diagram of 7xxx aluminum alloy prepared in comparative example, wherein (a) is comparative example 1, and (b) is comparative example 2; Figure 51-3 and Comparative Example 1-2 are graphs showing changes in hardness of the alloys prepared at 150° C. for 48 hours. Figure 6 1-3 and comparative examples 1-2 are hardness changes of the alloys prepared at 200° C. for 48 hours; Figure 7 This is a graph showing the hardness change of the alloys prepared in Examples 1-3 and Comparative Examples 1-2 when kept at 250°C for 48 hours. DETAILED DESCRIPTION
[0012] The present invention will be further described in detail below with reference to the accompanying drawings and specific examples. The following examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Example 1
[0013] The composition (weight ratio) of the raw materials provided in this embodiment is shown in Table 1.
[0014] Table 1
[0015] Example 1: The alloy was melted according to the composition ratios shown in Table 1 and homogenized at 350°C for 5 hours, followed by a 10-hour hold at 470°C. The alloy was then air-cooled at room temperature for quenching. After homogenization, the alloy was rolled at 420°C for 1 hour, followed by multiple hot-rolling passes with a 5% reduction per pass and a total reduction of 70%. The alloy was then air-cooled to room temperature and then cold-rolled at room temperature for multiple passes with a 5% reduction per pass and a total reduction of 50%. The cold-rolled sample was solution-treated at 350°C for 2 hours, followed by a 2-hour hold at 475°C. The alloy was quenched in water at 25°C. The aging process then followed, specifically, as follows: Step 1) The sample was held at 120°C for 1 hour. Step 2) The sample from the previous step was pre-deformed by 5% tensile strain (performed at room temperature using a tensile machine, removed from the machine after the hold, and then stretched). After the stretching was complete, the sample was placed in a furnace for further aging. Step 3) Keep the sample from the previous step at 120°C for 24 hours. The sample is placed in the furnace after the temperature reaches 120°C.
[0016] The high-strength and softening-resistant 7xxx series aluminum alloy for nuclear power obtained in this embodiment has significant resistance to overheating softening at 150-250°C and 200-250°C, and can be used in lightweight high-temperature structural materials for nuclear power.
[0017] Example 2 The composition (weight ratio) of the raw materials provided in this embodiment is shown in Table 2.
[0018] Table 2
[0019] The difference between Example 2 and Example 1 is that different types of microalloying elements are added, and the preparation method is the same.
[0020] Example 3 The composition (weight ratio) of the raw materials provided in this embodiment is shown in Table 3.
[0021] Table 3
[0022] The difference between Example 3 and Example 1 is that different types of microalloying elements are added, and the preparation method is the same.
[0023] Comparative Example 1 The composition (weight ratio) of the raw materials provided in this comparative example is shown in Table 4.
[0024] Table 4
[0025] The difference between Comparative Example 1 and Example 1 is that the micro-alloy components are removed and only the main alloy components are used. The preparation method is the same as that of Example 1.
[0026] Comparative Example 2 The composition (weight ratio) of the raw materials provided in this comparative example is shown in Table 5.
[0027] Table 5
[0028] Comparative Example 2 has the same alloy composition as Example 1. The preparation method differs from the aging process in Example 1. Aging process for Comparative Example 2: Step 1) Hold the sample at 120°C for 1 hour. Step 2) Hold the sample from the previous step at 120°C for 24 hours. This comparative example utilizes a conventional single-stage aging method. Specifically, after the furnace temperature is raised to 120°C, the sample is placed in the furnace and held at this temperature for 25 hours.
[0029] Examples 1, 2, 3, and Comparative Examples 1 and 2 were characterized using spherical aberration-corrected transmission microscopy to observe the size and formation of quintic-symmetric quasicrystals. Hardness tests were performed using a microhardness tester after heating Examples 1, 2, 3, Comparative Example 1, and 2 at 150°C, 200°C, and 250°C for different periods of time to compare the high-temperature softening resistance of the 7xxx aluminum alloys disclosed herein.
[0030] Figure 1-Figure 2Figures 2 and 3 show the microstructures of the alloys obtained in Examples 1, 2, and 3, as well as Comparative Examples 1 and 2. It can be seen that for Examples 1-3, after the addition of the microalloying elements designed by the present invention and the corresponding aging process, the nanoreinforced phases are all relatively small, with a few being relatively coarse. For Comparative Example 1, since the composition does not include the microalloying elements designed by the present invention, the nanoreinforced phases of the resulting alloy material are generally larger after the same aging process. For Comparative Example 2, although the composition is the same as that of Example 1, the aging process uses a conventional aging process, and the nanoreinforced phases of the resulting alloy material are also larger than those of Examples 1-3 of the present invention.
[0031] Figure 3-Figure 4 The reasons for the significant difference in the size of the nano-precipitated phases in the embodiments and the comparative examples are demonstrated. For Examples 1-3, it can be seen that the ends of the nano-reinforced phases are regulated to form a five-fold symmetric quasicrystal structure. The left end of the typical nano-reinforced phase shown in Example 1 forms a five-fold symmetric quasicrystal structure, so that the typical reinforcement phase size is about 9.4nm long and about 2.4nm wide. The right end of the typical reinforcement phase shown in Example 2 forms two five-fold symmetric quasicrystal structures, so that the typical reinforcement phase size is about 9.2nm long and about 2.4nm wide. The typical reinforcement phase shown in Example 3 forms a five-fold symmetric quasicrystal structure on each side, so that the typical reinforcement phase size is only about 2.4nm long and about 1.6nm wide. For the relatively coarse reinforcement phases shown in Comparative Examples 1 and 2, no five-fold symmetric quasicrystal structure is visible at its left and right ends. This shows that the five-fold symmetric quasicrystal structure regulated by the alloy composition designed by the present invention and the corresponding aging process has a controlling effect on the size of the nano-reinforced phase.
[0032] Figure 5-Figure 7 The hardness changes of all embodiments and comparative examples are shown when kept at 150°C, 200°C, and 250°C for 48 hours. Figure 5 It shows that when kept at 150°C, the hardness of the alloy materials obtained in Examples 1-3 decreases by about 5-6 Hv after being kept at 150°C for 48 hours, while the hardness of the alloy materials obtained in Comparative Examples 1-2 decreases by about 20 Hv after being kept at 150°C for 48 hours. Figure 6 It shows that under the condition of keeping at 200°C, the hardness of the alloy materials obtained in Examples 1-3 decreased by about 10 Hv after being kept at 48 h, while the hardness of the comparative example 1-2 decreased by more than 20 Hv. Figure 7 The results show that after 48 hours of holding at 250°C, the hardness of the alloys obtained in Examples 1-3 decreased by approximately 20-25 Hv, while the hardness of the comparative example decreased significantly at this temperature, reaching approximately 100 Hv after 48 hours of holding. This demonstrates that the alloys disclosed in this invention exhibit significantly greater resistance to high-temperature softening than conventional 7xxx series aluminum alloys.
[0033] Example 4 The composition (weight ratio) of the raw materials provided in this embodiment is shown in Table 6.
[0034] Table 6
[0035] The alloy of this embodiment is smelted according to the composition ratio in Table 6, and the prepared metal material is smelted at a high temperature of 700°C in a smelting furnace. A certain amount of slag remover is added, and the slag remover is a chloride-fluoride salt composite slag remover. The added amount is equivalent to 0.1wt% of the metal material. The liquid metal is deslagging and argon degassing and refined. Specifically, the slag remover is evenly sprinkled on the surface of the liquid metal and slightly stirred. Specifically, a graphite rotor is used for stirring at a speed of 400r / min to promote slag and gas separation. After stirring, the material is allowed to stand for 10 minutes to skim off the slag. The liquid metal is then poured into a mold to solidify to form a 7xxx aluminum alloy ingot material, and is homogenized. The treatment process is to keep it at 250°C for 6 hours, then keep it at 450°C for 24 hours, and the quenching process uses air cooling at room temperature. After homogenization, the sample undergoes rolling, holding at 450°C for 5 hours. This is followed by multiple hot rolling passes with a 10% reduction per pass and a total reduction of 50%. The sample is then air-cooled to room temperature and then cold-rolled at room temperature with a 10% reduction per pass and a total reduction of 80%. The cold-rolled sample undergoes solution treatment, holding at 250°C for 3 hours, followed by a 5-hour hold at 480°C. The sample is quenched in water at 80°C. The aging process then proceeds, as follows: Step 1) Hold the sample at 100°C for 1 hour. Step 2) Pre-deform the sample from the previous step by 2% (at room temperature, using a stretching machine, then removed from the stretching machine, stretched, and then placed in a furnace for further aging). Step 3) Hold the sample at 180°C for 100 hours. The characteristics of Step 3 are that the sample is placed in the furnace after the furnace temperature reaches 180°C.
[0036] The high-strength and softening-resistant 7xxx series aluminum alloy for nuclear power obtained in this embodiment has significant resistance to overheating softening at 150-250°C and 200-250°C, and can be used in lightweight high-temperature structural materials for nuclear power.
[0037] Example 5 The composition (weight ratio) of the raw materials provided in this embodiment is shown in Table 7.
[0038] Table 7
[0039] The alloy of this embodiment is smelted according to the composition ratio in Table 7, and the prepared metal material is smelted at a high temperature of 760°C in a smelting furnace. A certain amount of slag remover is added, and the slag remover is a chloride-fluoride salt composite slag remover. The added amount is equivalent to 0.3wt% of the metal material. The liquid metal is deslagging and argon degassing and refined. Specifically, the slag remover is evenly sprinkled on the surface of the liquid metal and slightly stirred. Specifically, a graphite rotor is used for stirring at a speed of 600r / min to promote slag and gas separation. After stirring, the material is allowed to stand for 30 minutes to skim off the slag. The liquid metal is then poured into a mold to solidify to form a 7xxx aluminum alloy ingot material, and is homogenized. The treatment process is to keep it at 400°C for 5h, then keep it at 460°C for 18h, and the quenching process uses air cooling at room temperature. After homogenization, the sample was rolled at 430°C for 3 hours, followed by multiple hot rolling passes with a 7% reduction per pass and a total reduction of 80%. The sample was then air-cooled to room temperature and then cold rolled at room temperature with a 7% reduction per pass and a total reduction of 60%. The cold-rolled sample was solution treated at 400°C for 2 hours, followed by a 3-hour hold at 480°C. The sample was quenched in water at 50°C. The aging process then began, as follows: Step 1: Hold the sample at 150°C for 1 hour. Step 2: Pre-deform the sample from the previous step by 8% tensile strain (performed at room temperature using a tensile machine, removed from the machine, and then stretched. After the stretching is complete, the sample is placed in the furnace for further aging). Step 3: Hold the sample at 150°C for 50 hours. The characteristics of Step 3 are that the sample is placed in the furnace after the furnace temperature reaches 150°C.
[0040] The high-strength and softening-resistant 7xxx series aluminum alloy for nuclear power obtained in this embodiment has significant resistance to overheating softening at 150-250°C and 200-250°C, and can be used in lightweight high-temperature structural materials for nuclear power.
[0041] Example 6 The composition (weight ratio) of the raw materials provided in this example is shown in Table 8.
[0042] Table 8
[0043] The rest is the same as Example 1.
[0044] Example 7 The composition (weight ratio) of the raw materials provided in this example is shown in Table 9.
[0045] Table 9
[0046] The rest is the same as Example 1.
[0047] Comparative Example 3 The only difference between this comparative example and Example 1 is that the sample was subjected to 1% tensile pre-deformation during the aging process. This comparative example also obtained a coarse reinforcement phase, with no quintic symmetric quasicrystal structure visible at either end.
[0048] Comparative Example 4 The only difference between this comparative example and Example 1 is that the sample was pre-deformed by 9% tension during the aging process. This comparative example also obtained a coarse reinforcement phase, with no quintic symmetric quasicrystal structure visible at either end.
[0049] The hardness data of the examples of the present invention and the comparative examples at room temperature and after 250°C / 48h are shown in Table 10 below.
[0050] Table 10 Hardness data table
[0051] Hardness test standard: GBT9790-2020, method: Based on this standard, measure 10 points and take the average value as the hardness value of the point.
[0052] It should be understood that in order to streamline the present disclosure and aid understanding of one or more of the various inventive aspects, in the above description of exemplary embodiments of the invention, various features of the invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, this disclosed method should not be interpreted as reflecting an intention that the claimed invention requires more features than are expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in less than all of the features of the previously disclosed embodiments. Accordingly, the claims that follow the detailed description are hereby expressly incorporated into this detailed description, with each claim standing on its own as a separate embodiment of the invention.
[0053] Although the present invention has been described with respect to a limited number of embodiments, it will be apparent to those skilled in the art, having benefit of the foregoing description, that other embodiments are contemplated within the scope of the invention thus described. Furthermore, it should be noted that the language used in this specification has been selected primarily for readability and didactic purposes, rather than for the purpose of explaining or limiting the subject matter of the present invention. Consequently, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the present invention is intended to be illustrative rather than restrictive of the scope of the invention, which is defined by the appended claims.
[0054] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A 7xxx series aluminum alloy with high strength and softening resistance for nuclear power, characterized in that: The composition includes Zn: 6-12 wt.%, Mg: 1.0-6.0 wt.%, Cu: 0-3.0 wt.%, microalloying elements: 0.2-2.5 wt.% and the balance Al.
2. The 7xxx series aluminum alloy with high strength and softening resistance for nuclear power according to claim 1, characterized in that: The microalloying elements include one or two of Sc, Er, Y, Yb, Ag, Ca, Sb, Pb, Bi, and Te.
3. The 7xxx series aluminum alloy with high strength and softening resistance for nuclear power according to claim 1, characterized in that: The ends of the nano-reinforced phase in the alloy have a quintic symmetric quasicrystal structure.
4. The 7xxx series aluminum alloy with high strength and softening resistance for nuclear power according to claim 3, characterized in that: The length of the nano-reinforced phase is 2.4-9.4 nm and the width is 1.6-2.4 nm.
5. The 7xxx series aluminum alloy with high strength and softening resistance for nuclear power according to claim 4, characterized in that: The nano-reinforced phase is 2.4 nm long and 1.6 nm wide.
6. The 7xxx series aluminum alloy with high strength and softening resistance for nuclear power according to claim 1, characterized in that: When the alloy is kept at 150℃ for 48h, the hardness value decreases by 5-6Hv; When the alloy is kept at 200℃ for 48h, the hardness value decreases by 10Hv; When the alloy is kept at 250℃ for 48h, the hardness value decreases by 20-25Hv.
7. The method for preparing a high-strength and softening-resistant 7xxx series aluminum alloy for nuclear power according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. Prepare the materials according to the alloy mass percentage requirements; S2. Smelting the prepared metal material to obtain liquid metal; S3. The liquid metal is poured into the mold and solidified to form a 7xxx aluminum alloy ingot material; S4. The ingot material is homogenized by holding at 250-400°C for 5-6h, then at 450-470°C for 10-24h, and quenching by air cooling at room temperature. S5. The homogenized samples were subjected to rolling: the process was to heat at 420-450°C for 1-5 hours, perform multiple hot rolling passes with a reduction of 5-10% per pass and a total reduction of 50-80%, then air cool to room temperature, and then perform multiple cold rolling passes with a reduction of 5-10% per pass and a total reduction of 50-80%. S6. The rolled plate is solution treated at 250-400°C for 2-3 hours, followed by 475-480°C for 2-5 hours, and quenched in warm water at 25-80°C. S7. Aging treatment of the material after solution quenching: Step 1) Keep the sample at 100-150°C for 1 hour; Step 2) Perform 2-8% tensile pre-deformation on the sample prepared in the previous step; Step 3) Keep the sample from the previous step at 120-180°C for 24-100 hours.
8. The preparation method according to claim 7, characterized in that In step 3), the sample is placed in the furnace after the furnace temperature reaches the corresponding temperature in step 3).
9. Use of the high-strength and softening-resistant 7xxx series aluminum alloy for nuclear power according to any one of claims 1 to 6 in lightweight high-temperature structural materials for nuclear power.
10. A lightweight high-temperature structural material for nuclear power, characterized in that: The invention is prepared from the 7xxx series aluminum alloy with high strength and softening resistance for nuclear power as described in any one of claims 1 to 6.